Sense of Justice and Human Rights (HAM): Gus Dur's Leadership Concept - Inayah Priyatun; Khafidh Abadi; Jainul Arifin (State Islamic Institute of Palopo, 2023)
The plurality of the Indonesian people regarding race, ethnicity, culture and religion must involve the government to intervene to overcome it in the field. With Islam dominating the population in Indonesia, the author is interested in examining how the definition of Islam as a moderate religion is according to Gus Dur, a just leader who is trying to be implemented in Indonesia with such a diverse population. As well as the author also describes how the form of implementation that has been abandoned by Gus Dur's history. This study aims to raise Gus Dur's point of view on Islam, justice and human rights. Islam is a religion that is rahmatal lil 'alamin and moderate for the Indonesian state. Muslims spread a lot of positive things and harmony in the form of values from the Islamic religion itself. Indonesia as a democratic country, is led by a leader, namely the president and oversees many ministers, departments, institutions, assemblies and many more. The duty of a leader is to maintain the trust of the people, to sacrifice for the security and welfare of the people.